Mental healthcare in older adults with schizophrenia: results from 118 French public psychiatric departments. (6th July 2015) - Raucher-Chéné, Delphine; Hoertel, Nicolas; Béra-Potelle, Céline; Terrien, Sarah; Barrière, Sarah; Da Rin, David; Tran, Eric; Cuervo-Lombard, Christine; Portefaix, Christophe; Limosin, Frédéric
Abstract : The increased life expectancy in people with severe and persistent psychiatric illness, such as schizophrenia or bipolar disorder, has been predicted to substantially affect mental healthcare system (Bartels et al ., 2002 ) that must adapt to meet the needs of older adults (Jeste et al ., 1999 ). Development of specialized geriatric psychiatry services is thus needed.